Pea protein isolate ‐ soluble soybean polysaccharides electrostatic assembly: Effect of pH , biopolymer mass ratio, and heat treatment - Igartúa, Daniela (2024)
Background: In past years, thousands of protein-polysaccharide complexes have been studied to modify protein characteristics and functionality in food systems. However, the interaction between pea protein isolate (PPI) and soluble soybean polysaccharide (SSPS) has not been thoroughly characterized yet.Results: In the present work, the phase behavior of PPI and SSPS mixtures was analyzed as a function of PPI:SSPS mixing ratio (1:1 to 1:0.10) and pH (7.0 to 2.0), showing that these biopolymers could be electrostatically assembled at 1:1 to 1:0.25 mixing ratios and 4.0 to 3.0 pH values. Then, the characteristics of the PPI-SSPS complexes were studied before and after heating (90 °C, 30 min) by ζ-potential, surface hydrophobicity, protein solubility, particle size distribution, and physical stability for 56 days. By lowering the pH and PPI:SSPS mixing ratio, the complexes showed increased solubility, changed -potential, and higher physical stability. By heating, the complexes presented increased hydrophobicity and physical stability.Conclusion: Overall, PPI-SSPS complexes increased the protein solubility, reduced the particle size, and changed both the ζ-potential and the surface hydrophobicity with respect to PPI control, allowing stabilization of the colloidal system and broadening the possible applications of these high-quality proteins in acidic food systems.